The characteristics of cultural tourists who visit urban jewish heritage centres: the case study of visitors to the White Stork Synagogue in Wrocław - Duda-Seifert, Magdalena (Turyzm/Tourism, 2016)
Since the White Stork Synagogue in Wrocław has been restored, opened to visitors and become a part of the so-called District of the Four Faiths promoted by the city council, both the synagogue and its neighbourhood have become tourist attractions which support Wrocław’s image as a multicultural city. Therefore, the aim of the article is to identify the characteristics of tourists visiting the synagogue which could help understand the specific features of those attracted by urban Jewish heritage. As a result of research with the use of surveys, interviews and observation, the highly emotive cognitive approach of tourists has been determined as the dominant feature in this niche market. Moreover, its strongly international character and its specific age and education structure have been pinpointed. These features form the basis for the conclusion that the tourists attracted by urban Jewish heritage form a very specific niche market which can be targeted especially by large cities through the development of themed tourist products.